Morphophysiological responses and mechanisms of salt tolerance in four ornamental perennial species under tropical climate - Claudivan F. de Lacerda; Emanuele V. de Oliveira; Antonia L. R. Neves; Hans R. Gheyi; Marlos A. Bezerra; Carlos A. G. Costa (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Salinity affects growth and quality of ornamental plants, but studies on mechanisms of salt tolerance in these plants are scarce, particularly under tropical climate conditions. Thus, the morphophysiological leaf responses of four tropical ornamental species were studied, in order to identify the mechanisms involved in the tolerance to salinity and their potentials to be irrigated with brackish water. The research was conducted in a greenhouse using a completely randomized block design, in a 10 x 4 factorial scheme, with four repetitions. The treatments consisted of ten levels of electrical conductivity of irrigation water (0.5; 1.0; 2.0; 3.0; 4.0; 5.0; 6.0; 8.0; 10.0 and 12.0 dS m-1) and four ornamental tropical species (Catharanthus roseus, Allamanda cathartica, Ixora coccinea, and Duranta erecta). At 30 and 60 days after the beginning of saline treatments (DAST), measurements of leaf gas exchange and chlorophyll index were performed. At 60 DAST, leaf area, specific leaf area, leaf area ratio, leaf succulence, Na+ and proline concentrations were measured. The physiological and morphophysiological responses of the leaves indicate that I. coccinea species has high capacity to grow under irrigation with saline water. Its higher tolerance to salinity is related to the lower concentration of Na+ in the leaves. Conversely, the sensitivity of D. erecta was associated with high Na+ and proline concentrations in leaves. The leaf concentration of proline showed to be an indicator more related to the sensitivity of ornamental plants to salt stress; however this relationship should not be generalized for all ornamental species studied.